2019
DOI: 10.1080/02656736.2019.1642521
|View full text |Cite
|
Sign up to set email alerts
|

Real-time fluorescence imaging for visualization and drug uptake prediction during drug delivery by thermosensitive liposomes

Abstract: Objective: Thermosensitive liposomal doxorubicin (TSL-Dox) is a promising stimuli-responsive nanoparticle drug delivery system that rapidly releases the contained drug in response to hyperthermia (HT) (>40 C). Combined with localized heating, TSL-Dox allows highly localized delivery. The goals of this study were to demonstrate that real-time fluorescence imaging can visualize drug uptake during delivery, and can predict tumor drug uptake. Methods: Nude mice carrying subcutaneous tumors (Lewis lung carcinoma) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…For example, ThermoDox® preclinical development information strongly suggests that the heating of the tumour needs to precede injection of the TSL 8 . Other studies have demonstrated effective treatment with FUS applied just before and then during infusion 46 , or immediately after injection 47 . In addition, the phase-III HEAT clinical trial computer modelling led to application of radiofrequency ablation 15 min post-infusion 48 and the TARDOX study indicated application of FUS shortly after infusion 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ThermoDox® preclinical development information strongly suggests that the heating of the tumour needs to precede injection of the TSL 8 . Other studies have demonstrated effective treatment with FUS applied just before and then during infusion 46 , or immediately after injection 47 . In addition, the phase-III HEAT clinical trial computer modelling led to application of radiofrequency ablation 15 min post-infusion 48 and the TARDOX study indicated application of FUS shortly after infusion 20 .…”
Section: Resultsmentioning
confidence: 99%
“…NIRF imaging allows monitoring of the level of iTSL within the tumour compared to the rest of the body 46 . We selected it as a semi-quantitative but robust method that was expected to significantly facilitate clinical translation 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have employed HT durations as low as 2 min, with 60 min on the upper end [1,14,15]. Since longer HT enhances drug release and delivery for TSL [1,22,24], we employed two HT durations: 60 min to maximize delivery, and 15 min to evaluate the impact of a reduced HT duration.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with photodynamic activation, nanotechnology assists in developing advanced PS/drug formulations, targeting therapeutics, controlled delivery, and drug release for the treatment of various diseases (Fig. 11) [272][273][274][275]. These are unique attributes of PDT using nanotechnology and perhaps other externally activated therapies.…”
Section: Nanotechnology and Targeting In Pdtmentioning
confidence: 99%